2016
DOI: 10.1177/1740774516643491
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing clinical evidence by proactively building quality into clinical trials

Abstract: Background:Stakeholders across the clinical trial enterprise have expressed concern that the current clinical trial enterprise is unsustainable. The cost and complexity of trials have continued to increase, threatening our ability to generate reliable evidence essential for making appropriate decisions concerning the benefits and harms associated with clinical interventions. Overcoming this inefficiency rests on improving protocol design, trial planning, and quality oversight.Methods:The Clinical Trials Transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…Our framework thus sought to identify elements common to clinical trials that could be subject to earlier planning as well as to failureexamination and root-cause analyses. We also wanted to draw parallels to other CTTI activities, particularly those related to Quality by Design (QbD), aimed at improving trials at earlier stages [21,22]. The framework delineates three areas essential to recruitment planning efforts: (1) trial design and protocol development, (2) trial feasibility and site selection, and (3) communication.…”
Section: Framework Development and Expert Meetingmentioning
confidence: 99%
“…Our framework thus sought to identify elements common to clinical trials that could be subject to earlier planning as well as to failureexamination and root-cause analyses. We also wanted to draw parallels to other CTTI activities, particularly those related to Quality by Design (QbD), aimed at improving trials at earlier stages [21,22]. The framework delineates three areas essential to recruitment planning efforts: (1) trial design and protocol development, (2) trial feasibility and site selection, and (3) communication.…”
Section: Framework Development and Expert Meetingmentioning
confidence: 99%
“…In both qualitative and quantitative results, local trial staff involvement in developing the protocol came up and was rated as the most helpful option for increasing protocol suitability. The importance of site staff involvement in trial planning has also been stressed in the literature [ 11 , 21 , 32 , 39 ]. Eastabrook et al state, “Given the important role of site staff for overall trial success it is critical to understand their preferences and experiences” [ 40 ], while Alsumidaie promotes trial site involvement to create clinical trials that work operationally while reducing risks [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…While feasibility of trial sites is routinely assessed, protocol suitability is a new concept and rarely considered. Meeker-O’Connell et al stress that improving protocol design, trial planning and quality oversight has a direct impact on inefficiencies like high costs and unsustainability [ 21 ]. With the rising complexity of trial protocols and the intense pressure on sponsors to accelerate development cycle times, suitability is becoming more important to alleviate execution burdens and ultimately improve trial conduct efficiency [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…and provide a feasibility score from options "Feasible and easy to achieve in current practice" (score 5), "Feasible but expensive or challenging" (4), "Not sure" (3), "Possible but cost or practical issues make it unworkable" (2), "Not possible at present" (1). We also asked respondents whether any of a pre-defined list of challenges might apply to implementing a given process: cost, time for trials unit staff, time for centre staff, logistical issues, legal or regulatory issues, other (specify).…”
Section: Stakeholder Consultation To Assess Feasibility Of Suggested mentioning
confidence: 99%
“…'errors that matter'. 1 The full methods and results are reported elsewhere. 17 TEMPER found that the majority of centres in both triggered visits and matched visits (those without concern) had at least one Major or Critical finding, questioning the efficacy of triggered monitoring as employed in these trials.…”
Section: Introductionmentioning
confidence: 99%